Engineering nanostructured cell micropatterns on Ti6Al4V by selective ion-beam inhibition of pitting. (1st May 2020) - López, R.; Ynsa, M.D.; de Pablo, P.J.; Lim, F.; Manso Silván, M.
Highlights: Wetting of Ti6Al4V is modified by ion irradiation. Pitting in HF after selective irradiation leads to nanotopographic contrasts. Concentration/surface tension of HF electrolyte influence Ti6Al4V etching. Etching in HF increases surface concentration of alumina. Pitting conditioned adhesion leads to ensheathing glia cell polarization. Abstract: We have modified Ti6Al4V at the micro and nanoscale by using ion beam irradiation with 5 MeV Si + ions through 1D micromasks. The passivation layer on irradiated areas inhibits hydrofluoric acid induced etching, leading to pitting contrasts. Surface microscopies and spectroscopies reveal that the nanotopographic modification correlates with a preferential titanium etching, and lead to dual surface free energy properties. The patterns are able to induce guidance of olfactory ensheathing glia cells, mainly through inhibition of adhesion on nanostructured areas, and could be attractive substrates for the induction of stimuli to neural cells under non voltaic polarization.